اختصاصات الولاية في مجال التعاون الدولي اللامزي بين النص والواقع - كبسة, عبد الحميد (University of Eloued جامعة الوادي, 2020)
يعتبر التعاون الدولي اللامركزي شكلا مستحدثا من أشكال العلاقات الدولية، ويرتكز على ممارسة الجماعات المحلية لاختصاصاتها في إب ا رم علاقات خارجية وفق ضوابط التشريع المعمول به في كل دولة للحفاظ على سيادة الدولة الت ا زماتها الدولية. أما في الج ا زئر، ورغم انطلاقه منذ الاستقلال مباشرة لكن شروطه الموضوعية والإج ا رئية ظلت غير محددة، تخضع اتفاقيته لرقابة قبلية مشددة من طرف الوصاية المركزية. حتى صدور القانون 12 07 الذي يتضمن قانون الولاية المادة 8 ال تي اعتبر ت الإطار التشريعي الأساسي لتأطير هذا النوع من العلاقات الخارجية وبإحالتها على التنظيم سنة بوسم المرسوم التنفيذي - 329 . يحدد كيفيات إقامة علاقات التعاون اللامركزي بين الجماعا ت الإقليمية الج ا زئرية والأجنبية. الذي في اطا ره أبرمت ولاية الوا دي اتفاقية توأمة مع ولاية توزر التونسية بهدف دعم التنمية المحلية لكن لم تظهر فعالية مخرجاتها على الواقع بسبب عدة عوامل من أهمها تقييد الاختصاص في مجال التعاون الدولي اللامركزي. والاحداث السياسية والصحية المستجدة.The decentralized international cooperation is considered as novelty form of the international relationships. It is based on the local groups' practice of their competences to conclude external relationships in accordance with the applicable regulations of the legislation in each country to preserve its sovereignty and its international commitments. As for Algeria, despite its inception since the independence immediately, but its substantive and procedural requirements remained unspecified, and its agreement are subject to strict tribal control by the central guardianship. Until the issuance of article 8 of law 12-07 that includes the state law, which was considered the basic legislative framework for framing this type of external relationships, with reference to the organization issued in 2017. The executive decree 17-329. It determines the modalities for establishing decentralized cooperation relationships between Algerian and foreign regional group. In this frame, El oued province entered into a twinning agreement with the Tunisian state of Tozeur with the aim of supporting local development, but the effectiveness of its outputs did not appear on the reality due to several factors, the most important of which is restricting jurisdiction in the field of decentralized international cooperation. And new political and health events.
مذكرة ماستر
Keywords: التعاون اللامركزي. الجماعات المحلية. التنمية المحلية. المرسوم التنفيذي 17-329: Decentralixed cooperation. Local communities, local development, executive decree 17-329.